Research on Accounting Treatment of China's Carbon Emission Right under Low Carbon Economy - Wei, Fei (Journal of Global Economy, Business and Finance, 2024)
Carbon accounting plays an important role in the balance between economic development and environmental protection. It is an effective tool to push enterprises to reduce emission. Under the guidance of the carbon peaking and carbon neutrality, along with the establishment and development of China's carbon emission trading market, the Ministry of Finance also issued the Interim Provisions on Accounting Treatment of Carbon Emission Trading to guide the standardized accounting treatment of relevant businesses of key emission enterprises in China. In this paper, the existing research on carbon accounting was discussed, and the views of the industry on the recognition and measurement of carbon emission quotas before and after the promulgation of the Provisional Provisions were reviewed. Moreover, the shortcomings of the Provisional Provisions were analyzed, hoping to contribute to the improvement of China's carbon accounting system and the development of the carbon emission trading market.